A expansão dos centros de atenção psicossocial (CAPS) e os indicadores de internações por transtornos mentais e comportamentais: uma análise utilizando o método propensity score matching - Araújo, Hyolitta Adrielle Costa de (2021)
The National Mental for Health Policy (PNSM) has developed through a strategy of the traditional model of hospitalization, for a model focused on substitutive services and preventive approach,which has the Centers of Psychosocial Attention (CAPS) as a fundamental strategic device to induce this model. Thus, the general objective of this research is to evaluate the impact of the expansion of CAPS on indicators of hospitalization for mental and behavioural disorders (TMC) in brazilian municipalities that were exposed to the program. Considering the availability of data referring to the CAPS expansion period, two groups of different periods were used for the evaluation, 2008 as the initial year of receipt of the program and 2019 as the last observed year. To assess this impact, the textit Propensity Score Matching method was applied through two result indicators, the average length of stay and the average cost of hospitalizations. The main results showed a positive impact of the CAPS on the average length of stay and the average cost of hospitalizations for TMC in the municipalities that received the program for the two periods analyzed. These findings corroborate the need at the policy management level to think of strategies to reduce the length of hospital stays when these are necessary, since in addition to the decrease in the level of individual well-being, and society, its impacts ranging health indicators to diverse economic issues, long-term hospitalizations are costly for the health system, generating pressure on its costs.